A Comparative Study of the Effect of Sodium Aluminate, Magnesium Oxide, and Calcium Hydroxide on the Concentration of Silicon Dioxide in RO Water Plants - Ibrahim A. Alsayer (Journal of Chemical Engineering of Japan)
The abundance of silica in water from wells is greater than in other sources of water; however, the silica in such brackish water has a considerable negative impact on the equipment which water flows through, and this effect is greater at the higher temperatures found in deep wells. High levels of silica also have a significant negative effect on Reverse Osmosis (RO) membranes used in treating well-water, thus high concentrations must be reduced to an acceptable level to protect the equipment and membranes. This study investigates three methods of reducing silica by chemical treatment in water purification plants and factories. These chemical methods are silica reduction by lime-soda softening; adding sodium aluminate; and reducing it using magnesium oxide. The study investigated the effect of different doses of these chemicals on the concentration of silica in different water samples. Laboratory Jar-tester experiments using different dosage of these precipitation chemical agents were conducted and the silica level was measured. An economic comparison study was also conducted between these three methods, investigating the cost of treating 30,000 cubic meters of water by each chemical method. It was found that treatment with magnesium oxide was the most economical of the three and could save about US$ 2.2 million annually.